IMPLEMENTASI METODE DESIGN THINKING DAN PRINSIP GESTALT PADA RANCANG BANGUN DASHBOARD SMART-FARM - Alvin Wiraprathama; I Made Widiartha; I Ketut Gede Suhartana; I Gusti Agung Gede Arya Kadyanan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2024)
Bali's agricultural sector experienced a notable downturn in growth during 2022 compared to the preceding year, which had seen substantial expansion. One of the key factors behind this decline was the limited adoption of digital farming practices in Bali. This underutilization of digital technologies in agriculture, including tools for crop monitoring, soil analysis, weather prediction, and market connectivity, likely contributed to decreased productivity and efficiency in farming activities. Addressing this issue could be pivotal for Bali to rejuvenate its agriculture sector and foster growth moving forward. To tackle this challenge, a smart farming dashboard has been developed specifically to address the needs of farmers in Bali. This dashboard boasts a user-friendly interface design and incorporates features tailored to assist farmers in Bali. The dashboard was crafted through the application of design thinking methodology, integrating Gestalt principles to optimize the user interface. The results of the dashboard's usability testing, as measured by the System Usability Scale (SUS), indicate a strong performance with a score of 79.75, reflecting its excellent usability.